2021
DOI: 10.1088/1674-1056/abeedf
|View full text |Cite
|
Sign up to set email alerts
|

Universal memory based on phase-change materials: From phase-change random access memory to optoelectronic hybrid storage*

Abstract: The era of information explosion is coming and information need to be continuously stored and randomly accessed over long-term periods, which constitute an insurmountable challenge for existing data centers. At present, computing devices use the von Neumann architecture with separate computing and memory units, which exposes the shortcomings of “memory bottleneck”. Nonvolatile memristor can realize data storage and in-memory computing at the same time and promises to overcome this bottleneck. Phase-change rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 339 publications
(372 reference statements)
0
6
0
1
Order By: Relevance
“…[40][41][42][43][44][45] The PCM operations, based on the reversible switching between the crystallized state and the disordered amorphous state of a chalcogenide alloy (typically a telluride), exhibit a marked contrast in the electrical conductivity and optical reflectivity, and are ultra-rapid, on the several ten-nanosecond timescales. [46][47][48][49][50][51] Moreover, experiments have revealed that the "priming" of crystalline nuclei in the amorphous state, which is denoted as the primed state, can lead to ultra-rapid set (crystallization) operations. [52][53][54] The primed state can be distinguished from the amorphous state with regard to their altered responses to thermal or electric stimuli, although a negligible variation occurs in the electrical conductance.…”
Section: Resultsmentioning
confidence: 99%
“…[40][41][42][43][44][45] The PCM operations, based on the reversible switching between the crystallized state and the disordered amorphous state of a chalcogenide alloy (typically a telluride), exhibit a marked contrast in the electrical conductivity and optical reflectivity, and are ultra-rapid, on the several ten-nanosecond timescales. [46][47][48][49][50][51] Moreover, experiments have revealed that the "priming" of crystalline nuclei in the amorphous state, which is denoted as the primed state, can lead to ultra-rapid set (crystallization) operations. [52][53][54] The primed state can be distinguished from the amorphous state with regard to their altered responses to thermal or electric stimuli, although a negligible variation occurs in the electrical conductance.…”
Section: Resultsmentioning
confidence: 99%
“…[194,210,211] Apart from the abovementioned resistive memristors based on ionic conductors and metal oxides, memristors composed of phase change materials (PCM) have also become the topic of intense investigations in recent years. [212][213][214][215] Analogous to the resistance variation controlled by the filament path in resistive memristors, the tuned amorphous and crystalline states can enable large resistance contrast in PCM memristors. [216,217] The nonvolatile memory based on PCM is particularly suitable for mapping analog synaptic weights due to the continuously variable conductance of the PCM.…”
Section: (13 Of 22)mentioning
confidence: 99%
“…While nonvolatile flash memories encounter charge storage problems originating from their fundamental scaling limits, which hinder their implementation on further size miniaturization . To overcome the bottleneck, enormous emerging nonvolatile memories, such as phase change random access memory, magnetoresistive RAM, and resistive RAM (RRAM) are viewed as the next promising candidates or alternatives by their excellent memory performance and requirements. Among them, RRAMs exhibit lots of benefits, including low fabrication cost, a simple metal–insulator–metal (MIM) structure, complementary metal–oxide–semiconductor compatibility, small effective cell size of 4 F 2 , fast switching speed, high cycling endurance, and favorable retention time. Transition metal oxide RRAMs such as HfO 2 , , TiO 2 , , NiO, , and ZnO , have been extensively studied and researched.…”
Section: Introductionmentioning
confidence: 99%